Drinking Water Supply without Use of a Disinfectant - Rajnochova, Marketa; Tuhovcak, Ladislav; Rucka, Jan (E3S web of conferences, 2018)
The paper focuses on the issue of drinking water supply without use of any disinfectants. Before the public water supply network operator begins to consider switching to operation without use of chemical disinfection, initial assessment should be made, whether or not the water supply system in question is suitable for this type of operation. The assessment is performed by applying the decision algorithm. The initial assessment is followed by another decision algorithm which serves for managing and controlling the process of switching to drinking water supply without use of a disinfectant. The paper also summarizes previous experience and knowledge of this way operated public water supply systems in the Czech Republic.